Transient Perivascular Inflammation of the Carotid Artery Syndrome - Yuta Hirose; Kiyoshi Shikino (Annals of Internal Medicine: Clinical Cases)
A previously healthy 52-year-old woman presented with left anterior cervical pain that had persisted for 10 days. Cervical magnetic resonance imaging revealed a high-intensity signal in the region exhibiting short-inversion-time inversion recovery; therefore, the patient was diagnosed with transient perivascular inflammation of the carotid artery (TIPIC) syndrome. TIPIC syndrome is a nonspecific inflammatory finding in the soft tissues surrounding the carotid arteries and should be included in the differential diagnoses of patients with acute anterior cervical pain.